Re-use of South African fly ash for CO2 capture and brine remediation. - Muriithi, Grace Nyambura (University of the Western Cape, 2021)
Philosophiae Doctor - PhD === Coal combustion accounts for 95% of electricity generation in South Africa while globally coal combustion for energy generation stands at 42%. It has been predicted that coal utilization for energy generation will continue due to its low cost and availability in huge quantities in different parts of the world. Additionally brine and gaseous emissions are produced in the power generation and coal combustion processes. In fact, it has been established that CO2 emissions from power plants are the main cause of the green-house effect leading to global warming. Mitigation of the effects of disposal of fly ash, brine and CO2 emissions is critical for sustainable energy generation from coal and environmental protection. The study investigated whether South African coal fly ash could be used for brine remediation and CO2 capture using fly ash based hydrotalcites and zeolites. Four main objectives were investigated. These were; firstly, to compare the natural CO2 capture potential of a power station ash dam with an accelerated ex-situ mineral carbonation process. Secondly, to probe the effect of accelerated ex-situ mineral carbonation on brine quality with regards to major, minor and trace elements concentration. Furthermore, the study investigated the feasibility of synthesizing hydrotalcites from fly ash by optimizing the synthesis parameters such as acid concentration, aging time, aging temperature, pH during aging, crystallization time and crystallization temperature. Finally the study compared the CO2 adsorption capacities of the fly ash based hydrotalcites with fly ash based zeolites NaA, and NaX. The natural carbonation potential of the wet disposed ash dam at Secunda was investigated by coring a 20 year old dam. Three cores (SI, S2 and S3) were obtained by air flush coring the dam along a geophysical line and establishing the geophysical profile of the three cores. The surface of the three cores was of medium resistivity with values between 9.3 and 12.2 nm while the midsections were of low resistivity with values ranging between 4 and 7 nm. The base section of core SI had a resistivity of 28.3 nm, that of S2 was between 16.2 and 21.4 nm and that of S3 between 12.2 and 16.2 nm; implying that SI had the lowest salt load while S3 had the highest salt content. Moisture content was observed to be high deeper down the profiles of S2 and S3 with samples appearing water logged while SI had the highest moisture content at the surface showing the inhomogeneity of the ash dam. The morphology of fresh fly ash taken from the ash collection hoppers at Secunda was observed to be spherical. Weathered ash from the ash dam showed irregularly agglomerated particles while accelerated ex-situ mineral carbonation resulted in the formation of acicular particles of calcite. Fresh ash, weathered ash and the accelerated carbonated ash were all class F with a sum total of silica, alumina and iron oxide totaling more than 70%. A reduction in silica and alumina content with instability of fly ash. Dumping of spent iron catalyst (resulting from the petrochemical operations as Sasol) on the ash dam led to an increase in Fe203 content of the weathered ash. Enrichment of Nb, Sr, Y, Th, Na, Cl, S04, K and S with natural carbonation as well as during accelerated ex-situ mineral carbonation was observed and was due to the contact of ash with brine during these two processes. Reduction of Zr, Rb, Pb, Ni, Co and V content of ash was observed with weathering. Mineralogically, all the ash samples had main phases of mullite, quartz, magnetite and hematite, with weathered and accelerated carbonated ash having additional phases of calcite. The aluminosilicious nature of the three ashes was identified by structural evaluation using Fourier transform infrared analysis which revealed that, bands associated with C-O in-plane and out of plane bending of carbonates was only visible in weathered and carbonated ash.